Effectiveness assessment of non-pharmaceutical interventions: lessons learned from the COVID-19 pandemic. (April 2023) - Lison, Adrian; Banholzer, Nicolas; Sharma, Mrinank; Mindermann, Sören; Unwin, H Juliette T; Mishra, Swapnil; Stadler, Tanja; Bhatt, Samir; Ferguson, Neil M; Brauner, Jan; Vach, Werner
Summary: Effectiveness of non-pharmaceutical interventions (NPIs), such as school closures and stay-at-home orders, during the COVID-19 pandemic has been assessed in many studies. Such assessments can inform public health policies and contribute to evidence-based choices of NPIs during subsequent waves or future epidemics. However, methodological issues and no standardised assessment practices have restricted the practical value of the existing evidence. Here, we present and discuss lessons learned from the COVID-19 pandemic and make recommendations for standardising and improving assessment, data collection, and modelling. These recommendations could contribute to reliable and policy-relevant assessments of the effectiveness of NPIs during future epidemics.